Monitoring breathing cracks of a beam-like bridge subjected to moving vehicle using wavelet spectrum - Khoa, Nguyen Viet (Vietnam Journal of Mechanics, 2013)
In this paper a wavelet spectrum technique for monitoring the breathing crack phenomenon of a beam-like bridge subjected to moving vehicle is presented. The stiffness of element with a breathing crack is modeled as a time dependent stiffness matrix using the finite element method. The stiffness matrix of the structure at each moment depends on the curvature of the structure at the crack position. The breathing crack phenomenon can be detected by analysing the instantaneous frequency (IF) of the system using the wavelet spectrum. When the crack depth is large, the crack area might be determined by the significant peak in the IF. The simulation results show that when the crack “breaths” the amplitude of the vibration obtained from the vehicle is smaller than in the case of an open crack. This is a warning when using the amplitude of the dynamic response to estimate the crack depth when there is a breathing crack in the structure. Therefore, it is important to distinguish the open crack and breathing crack to obtain a more accurate estimation of the crack depth. The results showed that crack with a depth as small as 10% of the beam height can be detected by the method. The proposed method can be applied with a noise level up to 10%.